Analisis Strategi Content Marketing pada PT. Saudagar Buah Indonesia Menggunakan Metode Six Sigma - Larasati Septya Rizqi; Irfan Ardiansah (Jurnal Rekayasa Sistem Industri, 2022)
This research is a field observation at PT. Saudagar Buah Indonesia, which is one of the companies that work on snacks known as fruit strips. Rebranded in February 2020, which coincided with the COVID-19 pandemic, PT. Saudagar Buah Indonesia experienced difficulties in marketing its products offline. Therefore, they maximized their marketing activities online. In their online marketing efforts, the marketing team of PT. Saudagar Buah Indonesia conducts various digital marketing strategies, including content marketing. The purpose of this research is to examine the advantages and disadvantages and provide improvements to the content marketing strategy run by the marketing team of PT. Saudagar Buah Indonesia. Six Sigma is an industry-accepted and proven methodology used for business process improvement. This methodology is known as a disciplined methodology for defining, measuring, analyzing, improving, and controlling the quality of products, processes, and transactions of every company, with the goal of almost all defects being eliminated through a stage known as DMAIC (Define, Measure, Analyze, Improve, and Control). Six Sigma methodology is carried out qualitatively by analyzing problems and controlling or improving each issue. This research proposes improvements to the content marketing strategies, where the gain is expected to enhance the quality as well as deficiencies.